Comparison of two polymerase chain reaction assays, DaAn Gene (DaAn Gene 2019-ncov) and Cepheid (Cepheid Xpert Xpress SARS-CoV-2) for Delta and Omicron variants of SARS-CoV-2 detection in Yaoundé, Cameroon - Martin Maidadi-Foudi; Marie Atsama-Amougou; Celestin Godwe; Emilande Guichet; Nadine L. Boutgam; Guy Roland Awoundza Metomo; Oumarou Goni Hamadama; Gilles-Fils Woguia; Yannick F. Ngoume; Dowbiss Meta Djomsi; Roméo Brice D. Djounda; Modeste Ngamaleu; et al. (Journal of Public Health in Africa)
Background: New severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants may affect diagnostic test accuracy.